Factors affecting voltage stability while integrating inverter based renewable energy sources into weak power grids. Issue 6 (27th December 2022) - Saleem, M. I.; Saha, S.; Ang, L.; Izhar, U.; Roy, T. K.
Abstract: With the emergence of renewable energy sources (RESs), the power grid all over the world is going through a paradigm shift. The inverter based RESs are replacing the conventional rotating synchronous generators and this trend is expected to continue in coming years. Consequently, the grid strength is decreasing, which can pose significant challenges on the grid stability, especially during integration of IRESs. This paper presents a thorough analysis on the integration challenges of IRESs in weak grids. The paper also presents a comprehensive investigation on the impacts of factors, such as available fault level at the point of interconnection (POI), feeder length and grid nature on the POI voltage, and maximum allowable power injection by IRES. This is followed by maximum allowable IRES power injection sensitivity analysis to quantify the impacts of the aforementioned factors. The paper concludes with a thorough case study on the IEEE 39‐bus test system to numerically show the impact of diminishing grid strength on the integration of IRESs. Abstract : With the emergence of renewable energy sources (RESs), the power grid all over the world is going through a paradigm shift. The inverter based RESs are replacing the conventional rotating synchronous generators and this trend is expected to continue in coming years. Consequently, the grid strength is decreasing, which can pose significant challenges on the grid stability, especially during integration of IRESs. This paper presents a thorough analysis on the integration challenges of IRESs in weak grids. The paper also presents a comprehensive investigation on the impacts of factors, such as available fault level at the point of interconnection (POI), feeder length and grid nature on the POI voltage, and maximum allowable power injection by IRES. This is followed by maximum allowable IRES power injection sensitivity analysis to quantify the impacts of the aforementioned factors. The paper concludes with a thorough case study on the IEEE 39‐bus test system to numerically show the impact of diminishing grid strength on the integration of IRESs.